2023
DOI: 10.1021/acs.jpcc.3c05423
|View full text |Cite
|
Sign up to set email alerts
|

Universal Radiative Lifetimes in the Long-Lived Luminescence of Si Quantum Dots

Tomáš Popelář,
Pavel Galář,
Filip Matějka
et al.

Abstract: Silicon quantum dots (SiQDs) represent a perspective light emitting material. Here, we show that their typical long-lived photoluminescence can be fully radiative. However, despite the fully radiative nature, the overall yield of light emission from SiQDs is still hindered by dark QDs, the understanding of which is only very limited so far. To address this problem, first, we experimentally quantify the dependence of radiative lifetimes on the emission photon energy and show that this dependence is universal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…5 and Table 2 limit the spectral tunability of the long-lived PL component. In our previous work, 38 we showed that the long-lived PL channel can be tuned in a wide range of emission photon energies. Other reports clearly suggest 11,14–20 that one important factor which limits the spectral tunability of the long-lived component is the exposure to oxygen.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…5 and Table 2 limit the spectral tunability of the long-lived PL component. In our previous work, 38 we showed that the long-lived PL channel can be tuned in a wide range of emission photon energies. Other reports clearly suggest 11,14–20 that one important factor which limits the spectral tunability of the long-lived component is the exposure to oxygen.…”
Section: Discussionmentioning
confidence: 89%
“…Since the oscillator strength of the transition decreases as the -space overlap of the electron–hole wavefunction decreases, the latter transitions are relatively slow (≈100 μs) and are responsible for the classical red emission in SiQDs, 7,45,46 which we investigated in more detail in our previous article. 38 In an ideal hypothetical case, the PL measured in an SiQD sample should reflect these two radiative pathways, as sketched in the schematic image in Fig. 1c.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations